Dark towers : Deutsche Bank, Donald Trump, and an epic trail of destruction - Enrich, David, 1979- (New York, NY : Custom House, 2020)
"A searing exposé by an award-winning journalist of the most scandalous bank in the world, including its shadowy ties to Donald Trump's business empire"--
Includes bibliographical references and index.
Keywords: Trump, Donald, -- 1946-; Deutsche Bank; Banks and banking -- Corrupt practices; Investment banking -- Corrupt practices